BẢO VỆ BỔ SUNG KHOANG THIẾT BỊ CỦA MÁY BAY SU-C BẰNG CÔNG NGHỆ KHÍ KHÔ TRONG ĐIỀU KIỆN NHIỆT ĐỚI VIỆT NAM - V.N., Sereda; Nguyễn, Hồng Dư; A.A., Svitich; Phạm, Duy Nam; Nguyễn, Hồng Phong (Tạp chí Khoa học và Công nghệ nhiệt đới, 2025)
ADDITIONAL PROTECTION OF NOSE COMPARTMENT OF THE Su-C AIRCRAFT EXPLOITED IN TROPICAL CONDITIONS OF VIETNAM BY USING THE AIR DRYING TECHNOLOGY This article presents the testing result while applicating the air drying technology developed by Vietnam - Russia Tropical Centre in one military unit for protecting nose compartment of the Su-C fighter aircraft exploited in tropical conditions of Vietnam. The technology was accomplished by using an air drying equipment called ITM-OY2 connected to the conditioning system of aircraft by a standard air duct. The test has been conducted for two months. It is shown that, the average value of relative humidity in the nose compartment has been reduced and held at roughly 55% compared to 70% in hangar and 75% outside respectively. It is recommended that this technology should be widely applicated in all air force squadron of Vietnam for protecting Su-C fighter aircraft against the negative impact of tropical climate.